A Comparison of the Minimal-Touch Technique and the Eversion Technique for Microvascular Anastomosis in a Rat Model - Blackburn, Collin W.; Vossoughi, Sarah R.; Ojo, Bukola; Gorroochurn, Prakash; Marboe, Charles C.; Akelina, Yelena; Strauch, Robert J. (Journal of Reconstructive Microsurgery, 2017)
Background During microvascular anastomosis, needle placement is facilitated by inserting the tips of the forceps into the lumen of the vessel, rather than grasping and everting the luminal wall, to minimize trauma to the vessel. This study examines whether the vessel wall can be grasped and everted during microvascular anastomosis without compromising surgical outcomes.Methods A total of 20 Sprague–Dawley rats weighing between 252 and 483 g were used. Bilateral anastomoses of the animals' femoral arteries (mean size: 0.90 mm) were performed using two different techniques: the classic minimal-touch approach and the eversion technique. The first 10 animals were survived for 48 hours and the second 10 animals were survived for 2 weeks. Patency was assessed immediately after surgery and just before sacrifice. Hematoxylin and eosin stains were performed and each anastomosis scored according to a grading rubric assessing endothelial cell loss, neointimal proliferation, medial necrosis, adventitial inflammation, and inflammation thickness.Results The patency rates of both techniques were identical (100%). There was no difference in the patency rates of anastomoses evaluated 48 hours after surgery (100%) and 2 weeks after surgery (100%). Histological outcomes between the minimal-touch technique and the eversion method were similar. The thickness of adventitial inflammation at 2 weeks was the only outcome found to be statistically different (p = 0.046) between the two treatments and this difference favored the eversion technique (i.e., less inflammation thickness).Conclusion The eversion method of performing microvascular anastomosis provides comparable results to the classic minimal-touch approach in rat femoral artery anastomoses.
Keywords: eversion; microvascular anastomosis; back-wall stitch